"Duch demokratycznego kapitalizmu" Michaela Novaka Jego analiza i ocena w kontekście etyki chrześcijańskiej - Świątkowski, Waldemar (Annales. Etyka w Życiu Gospodarczym, 2016)
The paper refers to Michael Novak’s book The Spirit of Democratic Capitalism. Inhis book Novak advances, among others, the thesis that in the light of the encyclicalLaborem Exercens, published by John Paul II (1981), one can speak about someconverging elements of Catholic and liberal social thought, e.g.: the creativity ofmodern labour, which would reflect, however, in the two doctrines the theologicalsymbols of the Creator and His creation. But this paper cools down the enthusiasmof Novak and in six analysed aspects seeks to show that, despite some convergencein the phraseology between “the spirit of democratic capitalism” and “the spirit ofChristian ethics”, there extends between them an essential abyss, which is the resultof basing each “spirit” on different models of ethics.